Must the courageous also be wise? an exploration of Plato's laches - Pasco, Marc Oliver D. (2016)
The Laches features two Athenian generals (Laches and Nicias) and Socrates discussing the essential meaning of courage. Laches defines it as “a certain perseverance of the soul,” while Nicias argues that it consists in “knowledge of what is to be feared and hoped for both in war and in all other matters.” This paper, with the aid of several Plato scholars, argues that although most scholars agree that Socrates does not present his own view of the matter, hence leaving the dialogue without a proper resolution, it may still be surmised that for Socrates, courage means willful yet wise perseverance.
Keywords: Courage -- Analysis